evaluación de tipos de estabilizante y porcentaje de grasa de la leche en la calidad fisicoquímica y sensorial del yogur - Véliz Pinargote, Carlos German (2018)
The purpose of this research was to assess the physicochemical and sensory properties of a yogurt made with 3 levels of fat and using two types of stabilizer. A 2x3 bifactorial completely randomized design (DCA) was used. Factor A: Types of stabilizers, 0.2% of CC-729 and 3% of Inulin; Factor B: 1% milk, 2.5% and 4% fat, which originated six treatments, in addition a control was included (whole milk + unflavored jelly), three repetitions were made, resulting in 21 experimental units of 2000 gr. The physicochemical variables analyzed were: Syneresis, viscosity, pH, acidity and ° Brix, whose results were evaluated by means of an analysis of variance in comparison to the control by Dunnett's significance test; resulting the factor A with more incidence on all the variables, besides the inulin presented better results; while factor B did not show significant differences over any variable. The sensory evaluation (sensory preference test), conducted by a panel of 75 untrained judges, results that were analyzed by means of the Friedman test showed a better behavior when fat increased in milk, the control and T5 being more acceptable (3% inulin with milk with 2.5% fat), it was also determined that there were significant differences among the treatments against the control.